ANTIBACTERIAL STUDIES OF ESSENTIAL OIL FROM THE FRESH LEAF OF LEMON GRASS CYMBOPOGON CITRATUS - Isyaka, Sani M.; Usman, Abdulazeez; Anyam, John V.; Labaran, Hajara S.; Bamidele, Musba’u I.; Abdullahi, Abdullahi Muhammad (FUDMA JOURNAL OF SCIENCES, 2024)
Cymbopogon citratus, belongs to Gramineae family. This study used a microwave-assisted hydro-distillation process to extract lemongrass essential oil and examined its antimicrobial qualities. Physical characteristics of the essential oils included a yellow color, a yield percentage of 4.67%, solubility in trichloromethane, and a lemony aroma. The disc diffusion method was used to assess the oil's effectiveness. Pseudomonas aeruginosa, Klebsiella oxytoca, Staphylococcus aureus, and Escherichia coli were all susceptible to the oil's concentration-dependent antibacterial qualities. 5.72 mmL/disc was the oil's most effective concentration against E. coli, while 1.43 mmL/disc was its least effective. The zone of inhibition shrank as the concentration of oil per disc dropped, indicating that the oil's activity against all species was concentration-dependent. At concentrations of 5.72 mmL/disc, 2.86 mmL/disc, and 1.43 mmL/disc, respectively, the zone of inhibition for E. coli was 24, 11.3, and 7.7 mm. For other creatures, the pattern is the same. Pseudomonas aeruginosa had the smallest zone of inhibition, measuring 7.0, 7.0, and 5.7 mm at concentrations of 5.72 mmL/disc, 2.86 mmL/disc, and 1.43 mmL/disc, respectively. Staphylococcus aureus was 13.3, 10.3, and 9.0 mm at concentrations of 5.72 mmL/disc, 2.86 mmL/disc, and 1.43 mmL/disc, while Klebsiella oxytoca was 11.3, 9.7, and 9.0 mm at concentrations of 5.72 mmL/disc, 2.86 mmL/disc, and 1.43 mmL/disc, respectively. These results imply that lemongrass essential oil may be a viable natural substitute for synthetic antibiotics, with potential uses in medical and food preservation. It is advised that additional bioassays be conducted and contrasted with the results obtained from alternative...
Keywords: Lemon grass; Essential oil; Organisms; Bacteria; Zone of inhibition